Padrões de movimentação de sabiás (Turdus ssp. Turdidae) em paisagens fragmentadas - Silveira, Natália Stefanini da [UNESP] (2015)
Large changes in ecosystems caused by fragmentation and habitat loss are the main threats to biodiversity in forested areas. They affect the populations that are already present and create even smaller fragments that change the landscape connectivity, which in turn influence the movement of the organisms. Frugivorous birds are among the main seed dispersers in fragmented areas due to their movement patterns. Thrushes are particularly important because they disperse many seed species. Using radio telemetry, this research investigated the movement patterns of thrushes (Turdus spp.) in rural areas of Itatiba, São Paulo. The aim was to infer about seed dispersal in altered landscapes focusing on the frequency with which thrushes move among fragments, the offset distances between those fragments, the landscape structures, and how those structures influence thrushes' movement pattern